2017
DOI: 10.1002/adma.201606112
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of Lyotropic Chromonic Liquid Crystals by Photoalignment with Photonic Metamasks

Abstract: Controlling supramolecular self-assembly in water-based solutions is an important problem of interdisciplinary character that impacts the development of many functional materials and systems. Significant progress in aqueous self-assembly and templating has been demonstrated by using lyotropic chromonic liquid crystals (LCLCs) as these materials show spontaneous orientational order caused by unidirectional stacking of plank-like molecules into elongated aggregates. In this work, it is demonstrated that the alig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 42 publications
1
52
1
Order By: Relevance
“…Earlier works to obtain large‐scale alignment follow substrate‐based approaches developed for thermotropic LCs, including alignment on polyimide (PI) substrates, rubbed glass, nanopatterned polymer films, self‐assembling monolayers, photosensitive surfaces and, very recently with photonic metamasks . In general, such substrates align thermotropics much better than LCLC solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier works to obtain large‐scale alignment follow substrate‐based approaches developed for thermotropic LCs, including alignment on polyimide (PI) substrates, rubbed glass, nanopatterned polymer films, self‐assembling monolayers, photosensitive surfaces and, very recently with photonic metamasks . In general, such substrates align thermotropics much better than LCLC solutions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, up to 8 lithography steps and sometimes electron-beam lithography are needed to achieve low f-numbers, [21][22][23] diffraction-limited performance, and over 90% efficiency. [31,33,35,36] Large-sized PB lenses with low f-numbers can be made by holography photopatterning with a refractive master lens, [31] while liquid crystal PB microlenses are still limited to large f-number (>10) [32,33] and no work has been able to show diffraction-limited quality.A range of techniques have been developed in recent years to align liquid crystal molecules into arbitrary designer orientation patterns, which are either based on photoalignments using digital micromirror device (DMD), [37,38] pixel-to-pixel direct laser writing, [30] holography interference [31] and plasmonic photo patterning, [39][40][41] or based on nanostructured surfaces by using nanoimprinting [33] or atomic force microscopy scribing. [13,14,21,[29][30][31][32][33][34] The PB microlenses made of liquid crystals are particularly attractive because of their close to 100% efficiency and switchable focal lengths.…”
mentioning
confidence: 99%
“…A range of techniques have been developed in recent years to align liquid crystal molecules into arbitrary designer orientation patterns, which are either based on photoalignments using digital micromirror device (DMD), [37,38] pixel-to-pixel direct laser writing, [30] holography interference [31] and plasmonic photo patterning, [39][40][41] or based on nanostructured surfaces by using nanoimprinting [33] or atomic force microscopy scribing. [42] These techniques have enabled various applications and research ranging from optical devices to programmable origami.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that periodic surface wrinkles can only be generated on top of a cholesteric liquid crystal under harsh conditions, 26,27 meanwhile the alignment direction of liquid crystal molecules can be patterned into complex spatially-varying structures with high precision. 28,29 Thus, it will be attractive to develop a simple means of preparing patterned cholesteric CNC films with controllable alignment and photonic properties.…”
Section: Introductionmentioning
confidence: 99%